Assessing bone maturity: compositional and mechanical properties of rib cortical bone at different ages - Bonicelli, Andrea; Kranioti, Elena F.; Xhemali, Bledar; Arnold, Emily; Zioupos, Peter (Elsevier, 2022)
Understanding what maturity entails for bone, when it arrives, and its pre- and post-maturity traits and properties are very important for understanding its evolution and physiology. There is a clear but fine distinction between the chronological age of bone (the age of its donor) and the tissue age of the bone packets it comprises at the microscopic level. Whole bone fragility changes with age due to mass and architecture effects, but so do the properties of bone at the tissue level. Tissue age and tissue-level properties are therefore increasingly attracting a great deal of attention recently. The present study investigated compositional and material changes in the hydroxyapatite crystals, the collagenous phase, changes in bone matrix composition and its nanoindentation properties and their decline with chronological age in later life. The aim was to track the age threshold at which cortical bone arrives at maturity and what happens following that threshold. To do so FTIR, DSC/TGA, XRD, nanoindentation and microindentation were used to investigate rib cortical bone material across a cohort of 86 individuals from one ethnic group with age spanning between 17 and 82 years. Results of this cross-sectional study showed a clear increase in mineral content relative to the organic and water contents across all ages. Furthermore, an increase in crystal size and consequent decrease in strain (coherence length) was detected associated with secondary mineralisation and an increase in carbonate substitution. Overall, we observe a number of modifications which contribute to a typical functional behaviour of bone showing an increase in both indentation modulus and hardness until the age of about 35 after which both of these properties decline gradually and concomitantly to other physicochemical changes and seemingly until the end of one's life.
Keywords: Maturity; Bone properties; Tissue age; Physicochemical characterisation; Nanoindentation